Depression in elderly women resident in a long-stay nursing home - Melissa Agostini Lampert (Dementia & Neuropsychologia)
Depression is the most common psychiatric disorder among the elderly: it is present in 23-40% of community-dwelling elderly and in 25-80% of institutionalized elderly. Depressive symptoms are most prevalent in elderly women because they more readily seek healthcare services, are more vulnerable to stress and live longer than men. OBJECTIVE: To investigate the prevalence of depression and its comorbidities in a long-stay nursing home (NH). METHODS: This retrospective, descriptive, epidemiological study was performed at a NH in southern Brazil and comprised the first part of a larger project to determine depression and its relationship with psychosocial factors in NH residents. Sociodemographic and medical data were obtained through the examination of medical files from November 2012 to January 2013. Depression was defined as the diagnosis reported by physicians in medical files and scores on the Geriatric Depression Scale (15-item version) above 5. Other clinical and psychiatric diagnoses were obtained from medical files. RESULTS: Out of a total of 142 elderly women, 51.4% had at least one psychiatric disorder, the most common being depression, affective bipolar disorder and mental retardation. Almost one third (32.3%) of the elderly women were depressed. The ward containing the highest number of cognitively and physically independent women contained 41.3% of the total depressed elderly. A total of 52.1% of all depressed elderly had other associated clinical or psychiatric disorders, with mental retardation and hypothyroidism being the most frequent. CONCLUSION: The prevalence of dementia was high in this NH. Further studies evaluating the psychosocial factors involved in depressed elders should be conducted in an effort to prevent depression and promote mental health in institutionalized elders.